(untitled) (The Agriculturists, 2010)
Field experiments were conducted during boro season of 2002 and 2003 at the Bangladesh Rice Research Institute (BRRI) farm having silty clay loam soil. Hybrid variety Sonarbangla-1 and BRRI hybrid dhan1 and modern inbred variety BRRI dhan29 were used in the experiments. Zero to 160 kg N ha-1 with 40 kg interval and different application schedules, chlorophyll meter based (SPAD35) N application and urea supper granules (USG) @ 80 kg N ha-1 were used as N treatments. During boro 2002, BRRI hybrid dhan1 had 10-15% higher tiller number, leaf area index (LAI) and crop growth rate (CGR) than Sonarbangla-1 and BRRI dhan29. Among the N managements, N9 (USG), N5 (160 kg N ha-1 with basal), N6 (160 kg N ha-1 without basal), and N7 (SPAD based N application with basal) showed 10-15% higher plant height, tiller hill-1, LAI and CGR. During boro 2003, Sonarbangla-1 and BRRI hybrid dhan1 had 10-15% higher plant height, tiller hill-1, LAI and CGR compared to the BRRI dhan29. Among the N management, N9 (USG), N5, N6, N7, N3 (120 kg N ha-1 with basal) and N4 (120 kg N ha-1 without basal) treated plots performed better in terms of growth. The LAI and CGR were reduced by 20-25 % at 60 DAT during 2003 compared to 2002 due to cold and the growth of BRRI dhan29 was restricted much.